Prove:
Using mathemetical induction:
P(n) = ![n^{3}+2n+3n^{2}](https://tex.z-dn.net/?f=n%5E%7B3%7D%2B2n%2B3n%5E%7B2%7D)
for n=1
P(n) =
= 6
It is divisible by 2 and 3
Now, for n=k, ![n > 0](https://tex.z-dn.net/?f=n%20%3E%200)
P(k) = ![k^{3}+2k+3k^{2}](https://tex.z-dn.net/?f=k%5E%7B3%7D%2B2k%2B3k%5E%7B2%7D)
Assuming P(k) is divisible by 2 and 3:
Now, for n=k+1:
P(k+1) = ![(k+1)^{3}+2(k+1)+3(k+1)^{2}](https://tex.z-dn.net/?f=%28k%2B1%29%5E%7B3%7D%2B2%28k%2B1%29%2B3%28k%2B1%29%5E%7B2%7D)
P(k+1) = ![k^{3}+3k^{2}+3k+1+2k+2+3k^{2}+6k+3](https://tex.z-dn.net/?f=k%5E%7B3%7D%2B3k%5E%7B2%7D%2B3k%2B1%2B2k%2B2%2B3k%5E%7B2%7D%2B6k%2B3)
P(k+1) = ![P(k)+3(k^{2}+3k+2)](https://tex.z-dn.net/?f=P%28k%29%2B3%28k%5E%7B2%7D%2B3k%2B2%29)
Since, we assumed that P(k) is divisible by 2 and 3, therefore, P(k+1) is also
divisible by 2 and 3.
Hence, by mathematical induction, P(n) =
is divisible by 2 and 3 for all positive integer n.
Answer:
yes
Step-by-step explanation:
by giving us a question and letting us answer it
Answer:
Step-by-step explanation
6n - 6 = 2 (n+1)
Simplify 2 (n+1)
6n - 6= 2n +2
Move all terms related to n to the left side of the equation
4n -6 =2
Move all terms not related to n to the right side of the equation
4n =8
Divide each term by 4 then simplify
n=2
Answer:
x = -3
Step-by-step explanation:
5x + 3 = 4x,
x + 3 = 0,
x = -3
Answer:
C. 1 - 2x > 13
Step-by-step explanation:
you just substitute